Environmental Competitiveness and Green Entrepreneurship: The Mediating Role of Generative Artificial Intelligence in Pakistan’s Manufacturing Sector - Muhammad Ahsan Iqbal; Asifa Muhammad Sabir; Hufza Iqbal (Inclusive Society and Sustainability Studies, 2026)
Green entrepreneurship has emerged as a strategic response to growing environmental pressures and competitive dynamics in Pakistan's manufacturing sector. This study empirically investigates how environmental competitiveness influences green entrepreneurship, with generative artificial intelligence (Gen-AI) adoption serving as a mediating mechanism. Grounded in Resource Orchestration Theory (ROT), the research examines: (1) the direct effect of environmental competitiveness on green entrepreneurship, (2) the direct effect of environmental competitiveness on Gen-AI adoption, (3) the direct effect of Gen-AI adoption on green entrepreneurship, and (4) the mediating role of Gen-AI adoption in the relationship between environmental competitiveness and green entrepreneurship. A cross-sectional survey was conducted with 250 employees from manufacturing firms across Pakistan (response rate = 62.5%). Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4. Results indicate that environmental competitiveness positively and significantly influences both Gen-AI adoption (beta = 0.257, p < 0.001) and green entrepreneurship (beta = 0.178, p = 0.019), while Gen-AI adoption significantly predicts green entrepreneurship (beta = 0.216, p = 0.006). Mediation analysis confirms partial mediation by Gen-AI adoption (indirect effect beta = 0.055, p = 0.014). The study contributes theoretically by extending ROT to the digital sustainability context and practically by offering actionable guidance for managers and policymakers in emerging economies seeking to leverage AI-enabled green strategies. Islamic ethical principles, namely khilafah, amanah, and mizan, are discussed as a conceptual lens that contextualizes responsible AI adoption within an ethical stewardship framework.